CONCEPTUAL MODEL FOR LITERACY IN A MULTICULTURAL ENVIRONMENT IN THE FIRST GRADE - Polihronov, Daniel Petrov (Journal of process management and new technologies, 2017)
In the article the author suggests a conceptual pedagogical model for literacy in a multicultural environment in the first grade. The empirical theoretical model is to be determined by: methodological aspects in Bulgarian Language and Literature education at the elementary stage; age characteristics and the development specifics of the child at an elementary school age and the sociocultural characteristics of the child’s family environment and their impact on her personality. The model for achieving literacy for pupils in the first grade in a multicultural environment is a prerequisite for achieving literacy in ethnic minority pupils; mastering the standard Bulgarian language and successful social inclusion of ethnic minority children.